A low-temperature AlN interlayer to improve the quality of GaN epitaxial films grown on Si substrates. Issue 46 (9th November 2016) - Lin, Yunhao; Yang, Meijuan; Wang, Wenliang; Lin, Zhiting; Li, Guoqiang
Abstract : The quality of GaN epitaxial films on Si substrates is significantly improved by employing a low-temperature AlN interlayer. Abstract : The quality of GaN epitaxial films on Si substrates is significantly improved by employing a low-temperature AlN interlayer. The relationship between the AlN interlayer growth temperature and the quality of GaN epitaxial films is systematically investigated. As the AlN interlayer growth temperature increases from 700 to 1000 °C, the crystalline quality of the GaN epitaxial films is firstly improved and then deteriorated. The GaN epitaxial film with the AlN interlayer grown at 800 °C shows the best crystalline quality, which is characterized by X-ray rocking curves with minimum full-width at half-maximum values of 370 and 452 arcsec for GaN (0002) and GaN (10–12), respectively. Further investigation reveals the fact that the low growth temperature of the AlN interlayer weakens the diffusion of Ga atoms from the AlGaN buffer layer into the AlN interlayer, thereby maintaining the lattice mismatch between the AlN interlayer and the GaN layer. The lattice mismatch facilitates the growth of 3-dimensional GaN which reduces the dislocation density effectively. This work provides a significant insight into the growth mechanism of GaN epitaxial films on Si substrates, which is critical for the fabrication of GaN-based devices on Si substrates.